Cristo, o arquétipo: o fenômeno psíquico da aparição à Maria Madalena na modernidade, segundo Carl Gustav Jung - Kasper, Glaucia (2024)
This research aims to reflect on the importance of the anthropological-philosophical foundation present in psychological practice. Specifically, the dissertation aims to address the unconscious psychic field in relation to the archetype of the Self and its manifestation as outlined in the writings of the physician and psychiatrist Carl Gustav Jung (1875-1961). It is characterized as a qualitative bibliographic research, which views the totality of the human psyche as consisting of two main fields: one conscious and the other unconscious. The unconscious field, with the Self as its regulating center, is chosen as the object of study. The archetype of the Self, projected by the unconscious and collective psyche of Western culture, is symbolically embodied in the image of Christ. The study is limited to the central archetype in its manifestation in the Christian myth, excluding the analysis of prefiguration from other religious diversities present in the West. In the Christ archetype, Jung identifies the symbolic manifestation of the Self. This can occur both on an individual and collective level, suggesting that such a psychic phenomenon may still occur today. The hypothesis that an archaic idea of God as the center, contained and prefigured in the unconscious and collective psyche of the West as Christ, holds great potential to become conscious through the assimilation of archetypal contents that reach consciousness through dreams and visions. Through the consideration of Jung’s theoretical writings, the research intends to guide the reader to the following problem: at which psychic level [conscious or unconscious] does the Western individual live the Christian myth? The dissertation also aims to highlight that the psychotherapeutic field requires the psychologist to adopt an analytical attitude capable of developing the virtues of the soul; such an attitude represents the improvement and development of the psychologist's personality, which then allows them to contribute to the psychological development of others. In light of the above, this study seeks to position: (1) the historical-philosophical context of analytical psychology; (2) in conjunction with the unconscious psychic field, the Self and its psychological role prefigured in Christ; (3) and, finally, to present an example of the manifestation of the archetype [Self], in its prefiguration in Christ, as narrated by the evangelist Saint John, contained in chapter 20, verses 1-18. The possible outcomes of this research consist of exposing the relevance of the manifestation of the Self archetype for the development of the psychic personality, in the process of making unconscious archetypal contents conscious, which aims, in this process, to lead the individual to a genuine and true encounter with their essence, that is, the becoming of the individual, but here, notably.